2002
DOI: 10.1016/s0896-6273(02)00724-9
|View full text |Cite
|
Sign up to set email alerts
|

Drosophila Lacking dfmr1 Activity Show Defects in Circadian Output and Fail to Maintain Courtship Interest

Abstract: Fragile X mental retardation is a prominent genetic disorder caused by the lack of the FMR1 gene product, a known RNA binding protein. Specific physiologic pathways regulated by FMR1 function have yet to be identified. Adult dfmr1 (also called dfxr) mutant flies display arrhythmic circadian activity and have erratic patterns of locomotor activity, whereas overexpression of dFMR1 leads to a lengthened period. dfmr1 mutant males also display reduced courtship activity which appears to result from their inability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
337
1
3

Year Published

2003
2003
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 266 publications
(376 citation statements)
references
References 55 publications
18
337
1
3
Order By: Relevance
“…The cellular neural phenotypes of dfmr1 mutant flies are qualitatively similar to the mammalian ones, with a common-but not universal-theme of dendritic and axonal overgrowth in CNS and PNS, as well as pathfinding errors [Zhang et al, 2001;Dockendorff et al, 2002;Morales et al, 2002;Lee et al, 2003;Michel et al, 2004;Pan et al, 2004]. The only neurons for which both axonal and dendritic morphologies have been examined in dfmr1 mutants are those of the mushroom bodies, a brain region well known for its role in many forms of associative learning and memory [Zars, 2000;Roman and Davis, 2001;Heisenberg, 2003].…”
Section: Case In Point: Drosophila Fragile X Mental Retardation 1 (Dfmentioning
confidence: 74%
See 3 more Smart Citations
“…The cellular neural phenotypes of dfmr1 mutant flies are qualitatively similar to the mammalian ones, with a common-but not universal-theme of dendritic and axonal overgrowth in CNS and PNS, as well as pathfinding errors [Zhang et al, 2001;Dockendorff et al, 2002;Morales et al, 2002;Lee et al, 2003;Michel et al, 2004;Pan et al, 2004]. The only neurons for which both axonal and dendritic morphologies have been examined in dfmr1 mutants are those of the mushroom bodies, a brain region well known for its role in many forms of associative learning and memory [Zars, 2000;Roman and Davis, 2001;Heisenberg, 2003].…”
Section: Case In Point: Drosophila Fragile X Mental Retardation 1 (Dfmentioning
confidence: 74%
“…This phenotype is reminiscent of the aberrant sleep patterns and elevated melatonin levels found in FXS males [Gould et al, 2000]. Finally, "courtship interest" is reduced in dfmr1 mutant males [Dockendorff et al, 2002], but the residual level can still be reduced further by courtship conditioning [McBride et al, 2005]. As with the memory defect, courtship interest was restored by mGluR blockade during development or adulthood, whereas the activity rhythm phenotype was not [McBride et al, 2005].…”
Section: Case In Point: Drosophila Fragile X Mental Retardation 1 (Dfmentioning
confidence: 96%
See 2 more Smart Citations
“…Physiological consequences of FMRP deficiency in the brain To improve our understanding of the physiological functions of FMRP in the brain, both the Fmr1-knockout mouse and the recently developed dfmr1-mutant flies have been studied [3,9,15,31,40,41]. Previous research has shown that the Fmr1-knockout mouse has subtle defects in behavior and spatial learning compared with wild-type mice [3].…”
Section: Ti Bsmentioning
confidence: 99%